Training information service specialists in the less favoured regions of the European Union (TRAIN-ISS) - I. Owens; F. Wood; T.D. Wilson; A.M.R. Correia (Information Research: An International Electronic Journal, 1996)
The expanding information infrastructure in Europe will increase the demand for high-quality, easily accessible and usable information services. At the same time, in the Information Society, there will be an increasing demand for professionals with skills, able to improve their potential through life long learning, accessing and using information sources available world-wide. Highly qualified information professionals are a crucial asset in any society to enable it to reap all the benefits and opportunities created by the Information Market. In the Less Favoured Regions (LFRs) of the European Union there is a shortage of education and training opportunities for information professionals to enable them to cope with the rapidly changing environment. It was to address this need for well qualified and trained information professionals that the TRAIN-ISS project was funded under the IMPACT 2 programme of the Commission of the European Communities